Nutritional Evaluation of Potato Meal on Growth Performance, Nutrient Utilisation, Blood Parameters and Economics in Growing Pigs - Singh, Jashandeep; Singh, Udeybir; Singh, Ashwani Kumar; Singh, Yashpal; Grewal, R.S. (Indian Journal of Animal Nutrition, 2022)
The experiment was conducted for nutritional evaluation of potato meal as an energy source in growing pigs. For the growth study, 12 pigs were distributed into 3 treatments for 60 days, each treatment having 4 pigs. T1 - Control diet, T2 – had potato meal, replacing 25% of crude protein contributed by maize. T3 - had potato meal replacing 50% of crude protein contributed by maize. The pigs of all experimental groups were weighed individually at 15 days intervals. Digestion trial and blood collection was done at the end of the experiment. Control diets fed pigs had better body weight gain, final body weight, average daily gain and FCR as compared to 25% and 50% supplementation and better digestibility parameters. Blood parameter shows no significant difference between the control (T1) group and the group fed with potatoes whereas blood parameters remained within the permissible limit. It was concluded that as the amount of potato meal supplementation increased, the gain in body weight and the digestibility of nutrients decreased.